Perkawinan Metaverse: Tinjauan Yuridis terhadap Perlindungan Hak Istri dan Anak dalam Perspektif Hukum Keluarga Islam - Siti Layyin Musfiqoh (Justicia Religia, 2025)
The development of metaverse technology has given rise to the phenomenon of "metaverse marriage," which challenges the framework of Islamic family law, particularly in protecting the rights of wives and children. This study aims to examine the legal implications of metaverse marriage from an Islamic Family Law perspective, identify legal challenges, and formulate an adaptive framework. Using a normative-empirical method with content and conceptual analysis, this study examines legislation, Islamic doctrine, and academic literature. The findings indicate that the concept of virtual marriage creates new vulnerabilities related to marital validity, rights to maintenance, custody, and protection from violence, which are not yet addressed by conventional law. Consequently, adaptive guidelines or regulations are needed to ensure justice and well-being, in line with the dynamic principles of Islamic law.